Optimization of the rural domestic waste recycling network based on the path planning site selection model - Chen, Jie; Wang, Yufei; Lei, Xiaoyu; Wang, Xi (Frontiers in Environmental Science, 2024)
Introduction In the context of rural revitalization strategies, effectively managing rural waste is a critical task for achieving ecological environmental sustainability. The current state of garbage collection and transportation is examined in this paper, focusing on the rural waste management practices in Dongfeng County, Liaoyuan City, Jilin Province, through mathematical modeling. Methods By analyzing the rural domestic waste collection network, the volume of waste generated at various points is fuzzified using the fuzzy mathematical theory. Results The results of path optimization for waste collection and transportation were derived from a case study, demonstrating the feasibility and practicality of the rural domestic waste recycling network model. Dicussion Additionally, sensitivity analysis was conducted to assess the impact of changes on the total cost. Potential solutions for rural waste recycling and treatment are offered in this paper, providing valuable insights for the development of a rural domestic waste recycling network in Jilin Province.